Побічні продукти виробництва рослинних олій як сировина для створення поверхнево-активних речовин та технічних систем - Bodachivska, L.Yu. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2021)
This work conducts a technical analysis of the current production and consumption of vegetable oils and some of the oily byproducts to determine the potential feedstock for the synthesis of non-food-competitive surfactants and surfactant-based systems. It defines the concentrated phosphatides (phosphatidic sludge) as no-/low- value streams, appropriately suited for chemical valorisation. The study further creates biobased surfactants by amidation of phosphatidic sludge derived from refinery of sunflower and rapeseed oils with monoethanolamine, N-(2-hydroxyethyl)ethylenediamine, or N,N’-bis(2-hydroxyethyl)ethylenediamine, under the action of calcium hydroxide as catalyst in excellent yields (95–98 %). Besides waste remediation, the use of phosphatides enabled to create the mixed surfactant compositions, comprising fatty acid alkanolamides and calcium glycerolphosphatides with improved solubility in organic non-polar solvents. With new surfactants, there have been created reversed emulsion systems, which can be potentially applied to the development and exploitation of gas and oil deposits are recommended for drilling wells, the disclosure of productive strata; perforation of wells and development of productive layers; blockage of gas, gas condensate and oil wells; elimination of manifestations and flow of gas in wells; limitation and elimination of waterways; cleaning of the hollow zone of wells and intensification of the inflow of hydrocarbon raw materials, which have been tested in laboratory and experimental industrial conditions, and a significant part of them have been introduced or tested on gas condensate fields. Creation of coordinated, effective and economical actions that should be formed in the state energy policy of Ukraine would facilitate the development of oil and gas companies, namely: increase of own oil and gas production; maximizing the potential of energy saving; diversification of external sources of supply; approximation of the parameters of the oil and gas industry to the norms and standards of the European Union.